IMPROVING STUDENTS’ READING COMPREHENSION THROUGH DIRECTED READING THINKING ACTIVITY (DRTA) METHOD - Kosmas Pangaribuan (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This study is aimed to know the influence of the DRTA (Directed Reading Thinking Activity) method on the student’s reading comprehension. Bauman proposes the DRTA Method. The design of the study is experimental research. In experimental research, the research consists of two classes; there are experiment and control classes. The research includes pre-test and post-test. The population is 107 and the sample 68 students. The author uses simple random sampling to determine the sample of the study. In the pre-test data, the mean score of the experiment class is 52,87, and the mean score of control class is 52,57. In post-test data, the mean score of experimental class is 76,81 and mean score of control class is 69,14. Based on the analysis the pre-test data, the value of Tcounted is 0,025 which is compared with Ttable is 1.668 or Tcounted < Ttable. It can be stated that there is no effect on pre-test data or the ability both of class are same. Next, based on the analysis of the post-test data, the value of Tcounted is 2,6595 that compared with Ttabel is 1.668 or Tcounted > Ttable , Ha is accepted. There is an effect of the DRTA (Directed Reading Thinking Activity) method on the student’s reading comprehension.